Vínculo familiar y su influencia en el proceso de adaptación en un paciente con insuficiencia renal crónica - Avilés Lúa, Yulet Melissa (2020)
The following research refers to the process of adaptation of a patient diagnosed with chronic renal failure and the incidence of the family bond, the family is a primary entity since it will provide support in the course of the patient's disease that is why it will be analyzed the family system is to say with whom the patient lives to discriminate if her difficulty in adaptation depends or is as a result of differences in her family. The adaptation process is a very difficult change that is generated in patients with chronic renal failure since this implies that they must modify their lifestyle to be able to adhere to the treatment without any difficulty. This case was carried out in the hemodialysis unit “Dial-Ríos” of Vinces specifically told a patient of this clinic. Various techniques were used, such as a clinical interview, psychometric tests and, in turn, tools such as the forms of the medical records that allowed recording the data collected and having a record of the information, which was then supportive when giving the result of both the tests as of the structural diagnosis of the patient. There is also a therapeutic scheme based on the rational emotional behavioral therapy created based on the information provided and detected that allowed identifying important points for the realization of this structure that will be very important for the change of the patient.